Life cycle assessment of alternative building materials using idematlightlca mobile app. (2022) - Saravanan, J.; Sridhar, M.
Abstract: In this paper, we have quantified the environmental impacts of different choices of conventional and alternative building materials for a 2BHK model residential building for above the plinth level construction using Life Cycle Assessment (LCA) standard procedures recommended by ISO 14040 – 2006 guidelines. The LCA was carried out using IdematLightLCA android app (Version 4.0) which is designed by Delft University of Technology, Netherlands. The comparisons were made between clay red bricks Vs sand lime bricks and reinforced cement concrete Vs bubble zoned light weight concrete with conventional and renewable energy resources inputs. The environmental impact categories analyzed were ranked on eco cost and on carbon footprint. The results confirmed that alternative materials along with renewable energy inputs proved to be more environment friendly and energy efficient than the conventional materials along with conventional energy inputs.